The Influence of Online Promotion and Consumer Lifestyle on the Decision to Buy Used Cars at Yusuf Mobilindo's Showroom in East Oku - Kurniawan, Refi; Siti Komariah Hildayanti; Tri Wulandari (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This study aims to analyze the influence of online promotions and consumer lifestyles on the decision to buy used cars at the Yusuf Mobilindo Showroom in East Oku. This type of research is quantitative descriptive. The technique of determining the number of samples uses the Hair et at formula, which is 10 times the number of all indicators, so that the number of research samples is 110 respondents. Data analysis uses data quality test, classical assumption test, and multiple linear regression analysis with t test (partial), F test (simultaneous), and R test. The results of the study show that Online Promotion has a positive and significant effect on the Decision of Buyers of used cars at the Yusuf Mobilindo Showroom as seen from the results obtained with a calculation value of 3,772 > a table of 1,981 with a significance level of 0.000 < probability of 0.05. Lifestyle has a positive and significant effect on the Decision of Buyers of used cars at the Yusuf Mobilindo Showroom, the results obtained with a calculation value of 2,908 > 1,981 with a significance level of 0.000 < probability of 0.05. Online promotions and lifestyle simultaneously have a positive and significant effect on consumer buyer decisions at the Yusuf Mobilindo Showroom. This can be seen from the results of the F test obtained a value of Fcal 19.627 > Ftable 3.08 with a value and significance level of 0.000 < 005. The result of the correlation value for the online promotion variable (X1) and lifestyle (X2) in relation to buyer decision (Y) is 0.518, so the relationship is positive. In the calculation of R Square, 0.268 was obtained, meaning that the combined influence of variables X1 and X2 on Y was 26.8%. The remaining 73.2% was influenced by other variables that were not studied.